PENGARUH OPASITAS BANK TERHADAP TINGKAT PERTUMBUHAN KREDIT DI MODERASI OLEH VARIABEL KAPITALISASI BANK, WHOLESALE FUNDING, MACROECONOMY CONDITION, DAN KUALITAS KREDIT (Studi Empiris pada Bank Umum Konvensional yang terdaftar di BEI 2018-2022) - Fatah, Abdoe Gamiyu; Puryandani, Siti (STIE PENA, 2024)
This study aims to investigate the effect of bank opacity on loan growth rates by considering the role of bank capitalization variables, wholesale funding, macroeconomic conditions, and credit quality as moderating factors. The empirical study was conducted on Conventional Commercial Banks listed on the Indonesia Stock Exchange (IDX) during the period 2018-2022. The research method uses multiple regression analysis and moderation techniques by utilizing financial and macroeconomic data sourced from bank financial reports in Indonesia. The results of this analysis can provide insight into the impact of bank opacity on loan growth, while explaining the extent to which the variables of bank capitalization, wholesale funding, macroeconomic conditions, and credit quality moderate the relationship. The findings of this study are expected to contribute to the understanding of the factors that influence credit growth in the banking sector, particularly in the context of bank opacity. The practical implications of this study can help regulators, bank management, and other stakeholders to develop appropriate policies to improve the stability and growth of the banking sector. Keywords: bank opacity, loan growth, bank capitalization, wholesale funding, macroeconomic conditions, credit quality.